Cody

Solution 1808856

Submitted on 7 May 2019 by Margaret Hoeller
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

Test Suite

Test Status Code Input and Output
1   Pass
nterms = 10; term0 = randi(10) ratio = (-1)^randi(2)*randi(10) correctsequence = term0*ratio.^(0:nterms-1); for position = 1:nterms errorsequence = correctsequence; errorsequence(position) = errorsequence(position) + (-1)^randi(2)*randi(50); [errorposition, truesequence] = find_error(errorsequence); assert(errorposition == position && isequal(truesequence, correctsequence), 'failed test 1 at position %d', position); end

term0 = 6 ratio = -4 r = -1.4118 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 r = -6.0000 -2.6667 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 r = -4.0000 -5.2083 -3.0720 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 r = -4.0000 -4.0000 -4.0833 -3.9184 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 r = -4.0000 -4.0000 -4.0000 -3.9896 -4.0104 -4.0000 -4.0000 -4.0000 -4.0000 r = -4.0000 -4.0000 -4.0000 -4.0000 -4.0098 -3.9903 -4.0000 -4.0000 -4.0000 r = -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -3.9982 -4.0018 -4.0000 -4.0000 r = -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0009 -3.9991 -4.0000 r = -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0003 -3.9997 r = -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -4.0000 -3.9999

2   Pass
nterms = 15; term0 = randi(10) ratio = (-1)^randi(2)*randi(10) correctsequence = term0*ratio.^(0:nterms-1); for position = 1:nterms errorsequence = correctsequence; errorsequence(position) = errorsequence(position) + (-1)^randi(2)*randi(50); [errorposition, truesequence] = find_error(errorsequence); assert(errorposition == position && isequal(truesequence, correctsequence), 'failed test 2 at position %d', position); end

term0 = 1 ratio = -7 r = -0.3182 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -41.0000 -1.1951 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -2.7143 -18.0526 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -6.0816 -8.0570 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0816 -6.9193 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -6.9800 -7.0200 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -6.9977 -7.0023 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -6.9996 -7.0004 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 r = -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000 -7.0000

Suggested Problems

More from this Author9